2013
DOI: 10.1016/j.eujim.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of general self-efficacy as a mediator in Taiji-induced stress reduction – Results from a randomized controlled trial

Abstract: Aim of the study: In this study we examined the effects of Taiji on perceived stress and general self-efficacy (GSE), and investigated the mediating role of a Taiji-induced GSE increase on Taiji-related reduction of perceived stress.Materials and methods: 70 healthy participants were randomly allocated either to the Taiji intervention group or the waiting list control group. The intervention lasted for 12 weeks comprising two Taiji classes per week. Before, shortly after, and two months after the intervention,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 55 publications
(61 reference statements)
3
13
0
2
Order By: Relevance
“…Specific mind-related transfer effects such as "increase of self-efficacy" and "improvement of stress management", which were the most frequently mentioned ones at tp1, were mentioned even more often at tp3 (see Table 2). This finding is in line with previous research that has shown immediate inhibiting effects of three months of Taiji training on psychobiological stress reactivity in healthy Taiji novices [15,24] . Furthermore, a prior study showed that a Taiji-induced reduction of perceived stress was mediated by an increase in general self-efficacy in response to the Taiji intervention, with participants reporting persistently increased general self-efficacy values two months after the intervention [24] .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Specific mind-related transfer effects such as "increase of self-efficacy" and "improvement of stress management", which were the most frequently mentioned ones at tp1, were mentioned even more often at tp3 (see Table 2). This finding is in line with previous research that has shown immediate inhibiting effects of three months of Taiji training on psychobiological stress reactivity in healthy Taiji novices [15,24] . Furthermore, a prior study showed that a Taiji-induced reduction of perceived stress was mediated by an increase in general self-efficacy in response to the Taiji intervention, with participants reporting persistently increased general self-efficacy values two months after the intervention [24] .…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in line with previous research that has shown immediate inhibiting effects of three months of Taiji training on psychobiological stress reactivity in healthy Taiji novices [15,24] . Furthermore, a prior study showed that a Taiji-induced reduction of perceived stress was mediated by an increase in general self-efficacy in response to the Taiji intervention, with participants reporting persistently increased general self-efficacy values two months after the intervention [24] . Our data now suggest that this also seems to be valid for a longer period of time: the prevalence of statements expressing an enhancement of self-efficacy in response to the Taiji intervention considerably increased over one year (see Table 3).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Dabei wurde im Vergleich zur Warteliste-Kontrollgruppe (n = 31) in der Taiji-Kursgruppe (n = 28) ein überzufällig höherer Anstieg der Werte für erwartete allgemeine Selbstwirksamkeit und Achtsamkeit - sowohl unmittelbar als auch 2 Monate nach Kursende - beobachtet. Ebenfalls signifikant höher fielen die Anstiegswerte für Self-Compassion der Taiji-Kursabsolventen 2 Monate nach Kursabschluss aus [10,11]. Diese Studienergebnisse weisen auf eine nachhaltig ressourcenaktivierende Wirkung von Taiji bei gesunden, überwiegend erwerbstätigen männlichen und weiblichen Studienteilnehmern hin.…”
Section: Ressourcenaktivierung Durch Taijiunclassified
“…Bezüglich der Wirkung von Taiji auf das allgemeine Stressempfinden konnte in der Interventionsgruppe eine im Vergleich zur Kontrollgruppe signifikante Abnahme des Summenwertes auf der Perceived Stress Scale (PSS) von Beginn bis Ende der Intervention sowie 2 Monate danach gemessen werden. Eine Mediatoranalyse ergab, dass diese Taiji-bedingte Abnahme des allgemeinen Stressempfindens durch den Anstieg der allgemeinen Selbstwirksamkeitserwartung vermittelt wurde [10]. …”
Section: Stressprävention Durch Taijiunclassified